Traditional use of medicinal plants in the boreal forest of Canada: review and perspectives - Uprety Yadav; Asselin Hugo; Dhakal Archana; Julien Nancy (BMC, 2012)
Abstract Background The boreal forest of Canada is home to several hundred thousands Aboriginal people who have been using medicinal plants in traditional health care systems for thousands of years. This knowledge, transmitted by oral tradition from generation to generation, has been eroding in recent decades due to rapid cultural change. Until now, published reviews about traditional uses of medicinal plants in boreal Canada have focused either on particular Aboriginal groups or on restricted regions. Here, we present a review of traditional uses of medicinal plants by the Aboriginal people of the entire Canadian boreal forest in order to provide comprehensive documentation, identify research gaps, and suggest perspectives for future research. Methods A review of the literature published in scientific journals, books, theses and reports. Results A total of 546 medicinal plant taxa used by the Aboriginal people of the Canadian boreal forest were reported in the reviewed literature. These plants were used to treat 28 disease and disorder categories, with the highest number of species being used for gastro-intestinal disorders, followed by musculoskeletal disorders. Herbs were the primary source of medicinal plants, followed by shrubs. The medicinal knowledge of Aboriginal peoples of the western Canadian boreal forest has been given considerably less attention by researchers. Canada is lacking comprehensive policy on harvesting, conservation and use of medicinal plants. This could be explained by the illusion of an infinite boreal forest, or by the fact that many boreal medicinal plant species are widely distributed. Conclusion To our knowledge, this review is the most comprehensive to date to reveal the rich traditional medicinal knowledge of Aboriginal peoples of the Canadian boreal forest. Future ethnobotanical research endeavours should focus on documenting the knowledge held by Aboriginal groups that have so far received less attention, particularly those of the western boreal forest. In addition, several critical issues need to be addressed regarding the legal, ethical and cultural aspects of the conservation of medicinal plant species and the protection of the associated traditional knowledge.